Grynfelt hernia - Armand Ugon, Alfredo; Lorenzelli, Juan Amílcar; Galarraga, José; Aliano, Franklin (Cirugía del Uruguay, 1977)
Superior lumbar hernias were described by Grynfelt in 1866. From that time until 1976, we find 257 such herniations in world literature, counting inferior and superior lumbar hernias. Anatomically, they emerge through Grynfelt's space, in the weak area of the dorsal branch of the 12th. intercostal space. 20 % are cóngenital and 80 % acquired. 26 % of the latter are traumatic and 54 % spontaneous. Clinically they are not very expressive and tumors predominate. Their treatment is surgical, involving anatomical repair, at times associated with rotation of flaps ar the use of grafts. Authors operated two cases.